Teacher Strategies to Overcome Initial Reading Diffcut-ies - Sari, Latifah Elfrida; Muhroji, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to describe teachers' strategies for addressing early reading difficulties. Methodology: The research adopts a descriptive qualitative approach. Data collection techniques include interviews, observations, and documentation. The study was conducted at SD N 3 Kudi, with research subjects consisting of the school principal, a first-grade teacher, six first-grade students, and their parents. Data validity was ensured through technique triangulation and source triangulation, with data analysis conducted using an interactive model. Results: The results reveal that: (1) Teacher strategies in instruction encompass lesson planning, the use of varied instructional strategies, and learning evaluation and follow-up, (2) Teacher approaches involve individual, group, and emotional approaches, and (3) Challenges to teacher strategies include factors related to interest, cognition, psychology, health, and environment. Applications/Originality/Value: Teachers play a crucial role in selecting strategies to enhance reading success in the classroom. Initial reading difficulties are a challenge for teachers in determining effective strategies. Strategies that are varied and tailored to students' needs can boost motivation in learning to read. Supportive facilities, along with good communication and cooperation between teachers and parents, can significantly enhance reading skills.